2022
DOI: 10.1002/gdj3.140
|View full text |Cite
|
Sign up to set email alerts
|

A review for Japanese auroral records on the three extreme space weather events around the International Geophysical Year (1957–1958)

Abstract: Solar Cycle 19 was probably the greatest solar cycle over the last four centuries and significantly disrupted the solar-terrestrial environments with a number of solar eruptions and resultant geomagnetic storms. At its peak, the International Geophysical Year (IGY: 1957(IGY: -1958 was organised by international collaborations and benefitted scientific developments, capturing multiple unique extreme space weather events including the third and fourth greatest geomagnetic storms in the space age. In this artic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…The February 1958 storms extended auroral visibility down to the Japanese Archipelago (Huruhata 1960;Saito et al 1994;Nakazawa 1999;Ninomiya 2013;Kataoka and Kazama 2019), whereas the individual auroral reports have been largely forgotten by the scientific community. However, copies of these individual Japanese records have recently been found in local meteorological offices, the National Astronomical Observatory, and Kiso Observatory of the University of Tokyo (Hayakawa et al 2023a), as shown in Fig. 33.…”
Section: Extreme Space Weather Events Around the Igymentioning
confidence: 99%
See 1 more Smart Citation
“…The February 1958 storms extended auroral visibility down to the Japanese Archipelago (Huruhata 1960;Saito et al 1994;Nakazawa 1999;Ninomiya 2013;Kataoka and Kazama 2019), whereas the individual auroral reports have been largely forgotten by the scientific community. However, copies of these individual Japanese records have recently been found in local meteorological offices, the National Astronomical Observatory, and Kiso Observatory of the University of Tokyo (Hayakawa et al 2023a), as shown in Fig. 33.…”
Section: Extreme Space Weather Events Around the Igymentioning
confidence: 99%
“…Fig. 34Auroral visibility during the extreme space weather events in September 1957 and February 1958 according to Japanese auroral reports, as reproduced fromHayakawa et al (2023a) …”
mentioning
confidence: 99%
“…Archival investigations of the historical magnetic measurements allow us to extend quantitative analyses for great magnetic storms beyond the International Geophysical Year (Mursula et al 2008;Lockwood et al 2018;Love et al 2019aLove et al , 2019bHayakawa et al 2023b). These studies have estimated a minimum disturbance-storm-time (Dst) index (Sugiura 1964;Sugiura & Kamei 1991) for the extreme storm of 1921 May of ≈−907 ± 132 nT (Love et al 2019b), comparable to the disturbance variation for the Carrington storm at Bombay of ≈−949 ± 31 nT (Hayakawa et al 2022a; see also Siscoe et al 2006;Cliver & Dietrich 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the solar-induced magnetic storms pose a systemic threat to the electrical power grids. However, it is challenging to study such extreme space weather events because of their low occurrence (Riley & Love 2017;Usoskin 2017;Gopalswamy 2018;Riley et al 2018;Miyake et al 2019;Chapman et al 2020aChapman et al , 2020bCliver et al 2022a) and the short chronological coverage of the modern databases that generally began with the International Geophysical Year in 1957-1958(Lanzerotti & Baker 2018Lanzerotti 2017;Hayakawa et al 2023b). To date, the best observed and documented extreme magnetic storm (in terms of solar origin, interplanetary disturbances, geomagnetic impact, and the resultant auroral extension) is that of 1989 March 13-14, which was the most intense storm in the space age (Allen et al 1989;Odenwald 2007;Lakhina et al 2013;Cid et al 2014;Saiz et al 2016;Boteler 2019).…”
Section: Introductionmentioning
confidence: 99%